Angiopoietin-1 Mimetic Nanoparticles for Restoring the Function of Endothelial Cells as Potential Therapeutic for Glaucoma - Raphael Mietzner; Ramona Pawlak; Ernst R. Tamm; Achim Goepferich; Rudolf Fuchshofer; Miriam Breunig (MDPI AG, 2021)
A root cause for the development and progression of primary open-angle glaucoma might be the loss of the Schlemm's canal (SC) cell function due to an impaired Angiopoietin-1 (Angpt-1)/Tie2 signaling. Current therapeutic options fail to restore the SC cell function. We propose Angpt-1 mimetic nanoparticles (NPs) that are intended to bind in a multivalent manner to the Tie2 receptor for successful receptor activation. To this end, an Angpt-1 mimetic peptide was coupled to a poly(ethylene glycol)-poly(lactic acid) (PEG-PLA) block co-polymer. The modified polymer allowed for the fabrication of Angpt-1 mimetic NPs with a narrow size distribution (polydispersity index < 0.2) and the size of the NPs ranging from about 120 nm (100% ligand density) to about 100 nm (5% ligand density). NP interaction with endothelial cells (HUVECs, EA.hy926) as surrogate for SC cells and fibroblasts as control was investigated by flow cytometry and confocal microscopy. The NP-cell interaction strongly depended on the ligand density and size of NPs. The cellular response to the NPs was investigated by a Ca2+ mobilization assay as well as by a real-time RT-PCR and Western blot analysis of endothelial nitric oxide synthase (eNOS). NPs with a ligand density of 25% opposed VEGF-induced Ca2+ influx in HUVECs significantly which could possibly increase cell relaxation and thus aqueous humor drainage, whereas the expression and synthesis of eNOS was not significantly altered. Therefore, we suggest Angpt-1 mimetic NPs as a first step towards a causative therapy to recover the loss of SC cell function during glaucoma.